The importance of removing interference caused by Darzalex® (daratumumab) in pre-transfusion testing (Journal of Health Sciences, 2024)
Introduction: Multiple myeloma (MM) is a hematologic malignacy characterized by the uncontrolled proliferation of abnormal plasma cells in the bone marrow. Darzalex® (daratumumab) has emerged as a highly effective therapeutic agent for MM, offering an additional treatment option for patients who have developed resistance to other therapies. However, the use of Darzalex® poses challenges in pre-transfusion testing due to its strong binding affinity of the monoclonal anti-CD38 antibody to CD38 protein, resulting in panreactivity with test erythrocytes and complicating the detection of erythrocyte alloantibodies. The objective of this case report is to outline the procedures, significance, and methodologies for mitigating this interference using the DaraEx® reagent.Case Report: We present the cases of three patients diagnosed with MM and treated with Darzalex® at our institution in 2023. Following the administration of Darzalex®, all three patients exhibited positive results on indirect antiglobulin tests (IAT). Cross-matching tests conducted with red blood cell concentrates also yielded positive results, with strengths ranging from 2+ to 3+. To eliminate interference, we used a specific DaraEx® reagent that utilizes Fab fragments of anti-CD38 to mitigate interference by masking CD38 on the cell surface. Subsequent application of this reagent resulted in negative IAT results for all three patients. However, one patient still displayed a weakly positive cross-matching test (<1+), suggesting that complete elimination of interference may not always be achievable with the DaraEx® method.Conclusion: Despite the availability of reliable methods such as dithiothreitol and the DaraEx® reagent for mitigating interference, complete success in eliminating interference remains elusive. This underscores the importance of implementing proactive measures to prevent interference. Patients undergoing Darzalex® therapy should undergo comprehensive immunohematological testing before medication administration. Given the increased need for blood transfusions in MM patients, ensuring the compatibility of blood products is essential for safe transfusion practices.